Microbiological Transformations of Δ(6a,10a)-Tetrahydrocannabinol - Fukuda, David (1977)
A screening program was conducted to find microorganisms that catalyze transformation reactions with cannabinoids. Three hundred fifty-eight cultures, consisting of 97 bacteria, 175 actinomycetes, and 86 molds, were incubated in media containing 0.5 mg of Δ(6a,10a)-tetrahydrocannabinol (Δ(6a,10a)-THC) per ml. After 120 h of cultivation, ethyl acetate extracts of the cultures were examined by thin-layer chromatography (TLC) for transformation products. About 18% of the cultures modified Δ(6a,10a)-THC. The ability to modify the substrate did not predominate among any particular group of microorganisms. After purification, the products from three cultures were analyzed by high-resolution mass spectrometry, 100-mHz proton magnetic resonance spectrometry, ultraviolet spectrometry, and infrared spectrometry. These spectral data indicated that a Mycobacterium sp. oxidized Δ(6a,10a)-THC to cannabinol and a diastereomeric pair of 6a-hydroxy-Δ(10,10a)-THC isomers; a Streptomyces sp. and a Bacillus sp. oxidized Δ(6a,10a)-THC to 7-keto-Δ(6a,10a)-THC and 4′-hydroxy-Δ(6a,10a)-THC, respectively. The occurrence of these products and the presence of others that have not yet been isolated or identified indicate that microbial transformation may be a useful tool for the preparation of new cannabinoids that have desirable pharmacological properties.